Simplify and solve the linear equation 15(y - 4) - 2(y - 9) + 5(y + 6) = 0

Asked by Aaryan | 1 year ago |  74

##### Solution :-

15(y - 4) - 2(y - 9) + 5(y + 6) = 0

⇒ 15y - 60 - 2y + 18 + 5y + 30 = 0 (Opening the brackets)

⇒ 18y - 12 = 0

⇒ 18y = 12

⇒ y = $$\frac{12}{18} = \frac{2}{3}$$

Answered by Sakshi | 1 year ago

### Related Questions

#### Solve the inequations and graph their solutions on a number line  – 1 < (x / 2) + 1 ≤ 3, x ε l

Solve the inequations and graph their solutions on a number line  – 1 < ($$\dfrac{x}{2}$$) + 1 ≤ 3, x ε l

#### Solve the inequations and graph their solutions on a number line – 4 ≤ 4x < 14, x ε N

Solve the inequations and graph their solutions on a number line – 4 ≤ 4x < 14, x ε N

#### Solve (x / 3) + (1 / 4) < (x / 6) + (1 / 2), x ε W. Also represent its solution on the number line.

Solve ($$\dfrac{x}{3}$$) + ($$\dfrac{1}{4}$$) < ($$\dfrac{x}{6}$$) + ($$\dfrac{1}{2}$$), x ε W. Also represent its solution on the number line.

If the replacement set is {-3, -2, -1, 0, 1, 2, 3}, solve the inequation $$\dfrac {(3x – 1) }{2} < 2$$. Represent its solution on the number line.
Solve the inequations ($$\dfrac{3}{2}$$) – ($$\dfrac{x}{2}$$) > – 1, x ε N